Pengaruh Pendekatan Science, Technology, Engineering, Mathematics (STEM) Berbantuan Articulate Storline 3 Blood At Work Terhadap Peningkatan Kemampuan Literasi Sains Siswa Sekolah Dasar - Rizky Purwatresna Senjaya; Hafiziani Eka Putri; Fitri Nuraeni (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Scientific literacy ability is one of the abilities that must be mastered by students in learning science. The low scientific literacy ability of elementary school students is the background of this research: 1) Assess and analyze the increase in scientific literacy skills of elementary school students who receive the STEM approach assisted by articulate storyline 3 blood at work as compared to students who receive learning with a conventional approach; 2) Knowing the effect of the STEM approach assisted by articulate storyline 3 blood at work on the scientific literacy abilities of elementary school students. The research method used was a quasi-experimental design with a non-equivalent pretest-posttest control group design on the topic of the circulatory system with a total of 60 students as subjects. The instrument used to obtain data before and after learning is the scientific literacy ability test instrument. Based on the research conducted, it can be concluded: 1) Increasing the scientific literacy skills of students who receive the STEM approach assisted by articulate storyline 3 blood at work is better than students who receive conventional learning, and 2) There is an effect of learning using the STEM approach assisted by articulate storyline 3 blood at work on students' scientific literacy abilities. Keywords: Science Technology; Engineering Mathematics (STEM), Articulate storyline 3 blood at work; Science Literacy Ability.